2020
DOI: 10.22270/jddt.v10i3-s.4169
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Antioxidant and Anti-obesity Activity of Salvia hispanica (Chia) Seeds Extracts

Abstract: Obesity is a condition in which large amount of fat is stored in adipose tissue. Obesity is the greatest risk for many diseases like coronary heart disease, type 2 diabetes millions associated with insulin resistance, arthritis disorder, hypertension and cancers. Currently, the available drugs for obesity have been associated with number of side effects when compared with allopathic drugs. Salvia hispanica was one of the member of Lamiaceae family, collected to study the antiobesity activity. Extraction of Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…were not isolated in the present study, the antibacterial activity of chia seed methanolic extract has been reported against S. aureus with an inhibition zone of 25 mm (Rubavathi et al, 2020). Dark chia seeds were used in the present study, and it has been reported that the synthesized silver nanoparticles of dark chia seeds had more antimicrobial activity against both E. coli (with 18. log CFU/g in both the control and treatments.…”
Section: Ta B L Ementioning
confidence: 70%
“…were not isolated in the present study, the antibacterial activity of chia seed methanolic extract has been reported against S. aureus with an inhibition zone of 25 mm (Rubavathi et al, 2020). Dark chia seeds were used in the present study, and it has been reported that the synthesized silver nanoparticles of dark chia seeds had more antimicrobial activity against both E. coli (with 18. log CFU/g in both the control and treatments.…”
Section: Ta B L Ementioning
confidence: 70%
“…There are many reports about S. hispanica L. seeds antiobesity action 10,[52][53][54][55][56] but no reports about aerial parts activity. The antiobesity activity is due to presence of poly phenolics, flavonoids and triterpenoides.…”
Section: Anti-obesity Activitymentioning
confidence: 99%
“…The antioxidant activity of the herbal plants was analysed by the DPPH and FRAP assay based upon the methodology of Ayyappadasan et al, 2017, Rubavathi et al, 2020. Extracts solution of 20, 40, 60, 80 and 100 µg/ml were prepared using their respective solvents for both standard and sample.…”
Section: Antioxidant Activitymentioning
confidence: 99%